2011
DOI: 10.3892/mmr.2011.590
|View full text |Cite
|
Sign up to set email alerts
|

An autophagy inhibitor enhances the inhibition of cell proliferation induced by a proteasome inhibitor in MCF-7 cells

Abstract: Abstract. The ubiquitin-proteasome system and the autophagy-lysosome pathway are the two main routes for eukaryotic intracellular protein clearance. Inhibition of proteasome activity leads to cell death. Due to the dual roles of autophagy in tumor cell survival and death, the effect of suppression of autophagy on breast cancer cells remains to be elucidated. We investigated whether inhibition of the proteasome is capable of inducing autophagy, and we assessed the effect of combined inhibition of the proteasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Proteasome inhibitors have been found to induce autophagy in a variety of cell types including prostate cancer (35) and melanoma (36). Induction of autophagy is generally thought to be a protective mechanism in cancer cells treated with proteasome inhibitors, and dual inhibition of the proteasome and autophagy has been shown to increase cell death (37). Increased death after dual inhibition of the proteasome and autophagy appears to be specific to transformed cells, possibly indicating an increased reliance of cancer cells on these cellular processes (38).…”
Section: Induction Of Apoptosis and Autophagy By Proteasome Inhibitormentioning
confidence: 99%
“…Proteasome inhibitors have been found to induce autophagy in a variety of cell types including prostate cancer (35) and melanoma (36). Induction of autophagy is generally thought to be a protective mechanism in cancer cells treated with proteasome inhibitors, and dual inhibition of the proteasome and autophagy has been shown to increase cell death (37). Increased death after dual inhibition of the proteasome and autophagy appears to be specific to transformed cells, possibly indicating an increased reliance of cancer cells on these cellular processes (38).…”
Section: Induction Of Apoptosis and Autophagy By Proteasome Inhibitormentioning
confidence: 99%
“…Proteasome inhibitors, including the multipathway inhibitor bortezomib, are promising agents for treatment of highly aggressive cancer ( 118 ). Studies performed on several cancer cell lines demonstrated that autophagy inhibitors can synergize with the cytotoxic effects of the proteasome inhibitors ( 119 121 ). Based on these preclinical data, a number of trials investigating autophagy inhibition in combination with proteasome inhibitors have been initiated.…”
Section: Autophagy and Response To Therapymentioning
confidence: 99%
“…Previous studies demonstrated that simultaneous proteasome and autophagy inhibition results in the accumulation of ubiquitinated proteins and thus in cytotoxicity [20,22,23]. Moreover, autophagy inhibition enhances the efficacy of many anticancer drugs, both in cell lines and in animal models [24][25][26][27][28], and synergistically increases bortezomib cytotoxicity in in vitro models of myeloma [29,30], colon carcinoma [31], and hepatocarcinoma [25]. Hydroxychloroquine (HCQ) is a well-known inhibitor of autophagy [32][33][34] and is commonly used to treat autoimmune diseases [35][36][37].…”
Section: Introductionmentioning
confidence: 99%